Results of morphological diagnosis of the aetiology of the diffuse lung disease syndrome. - Liskina, I. V.; Opanasenko, N. S.; Shalagay, S. M.; Zagaba, L. M.; Lysenko, V. I. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Diffuse Pulmonary diseases (DZL) is a heterogeneous group of diseases united on the basis of the characteristic radiological syndrome of pulmonary dissemination, which is manifested by widespread changes in both lungs of nodular, reticulate or mixed character with nonspecific clinical and altered pathological changes. Objective. To present the results of morphological diagnostics of the pathological process in the syndrome of pulmonary dissemination and to compare them with the final clinical diagnoses when applying different methods of biopsy sampling. Methods. 216 lung biopsies were selected for morphological diagnosis, followed by histological examination in 210 patients. Patients were divided into 4 groups depending on the method of obtaining biopsy material for histological examination (video assisted, open and transbronchial lung biopsy). Results. Most patients were with sarcoidosis 81 (37.5 ± 3.3)%metastatic lung damage was diagnosed for 36 (16.7 ± 2.5)% cases. Other diseases (various forms of fibrotic alveolitis, alveolar proteinosis, histiocytosis, diffuse pulmonary ossification, etc.) 25 (11.6 ± 2.2)% and pulmonary tuberculosis – 24 (11.1 ± 2.1) % cases. Conclusion. Prevalent patients were diagnosed with "disseminated process in lungs of unknown etiology" – 121 (57,6 ± 3,4)% of patients and "diffuse process in lungs in combination with syndrome of intrathoracic lymphadenopathy" – 41 (19,5 ± 2,7)% patient. According to the histological examination, sarcoidosis was the most common in 81 (37.5 ± 3.3)% of cases and metastatic lung injury was 36 (16.7 ± 2.5)%; Morphological examination of the pulmonary tissue in the case of pulmonary dissemination syndrome reveals numerous diseases of different etiology; or "narrows" the spectrum of pathology in the differential diagnosis of a particular disease.